PENDAMPINGAN GURU MELALUI KEGIATAN PENYULUHAN TERHADAP LABORATORIUM VIRTUAL BERBASIS PhET - Lissa Zikriana; Sharfina (LPPM Universitas Al Muslim, 2023)
This community service (PKM) activity is in the form of counseling for MIPA teachers of UPTD SMPN 3 Peusangan through training activities regarding virtual laboratories. Implementations of PKM activities for teachers were carried out through counseling in advance, and then proceed with the training. The benefits obtained from this community service activity include teachers being able to apply learning through a PhET-based virtual laboratory in learning and increasing students' abilities to continue to innovate to think logically, critically and creatively. The use of PhET simulations can help teachers easily explain subject matter to students, teachers can also directly explain abstract subject matter as proven through simulations. The PhET application can also prove things that are difficult to see from practicums carried out in real laboratories, and can even be used online or offline. The objectives of implementing this PKM activity were: 1) increasing teacher awareness of PhET-based virtual laboratory learning media, and 2) motivating students in learning, especially in mathematics and science lessons. The method of implementing the activity used the Focus Group Discussion (FGD) method. From the results of the implementation of outreach activities for PhET-based virtual laboratories for MIPA teachers at UPTD SMP Negeri 3 Peusangan it can be seen that: 1) teacher awareness of PhET-based virtual laboratory learning media has increased; and 2) in learning students are very enthusiastic about expressing their ideas.